Identification of Proteomic Biomarkers in Proliferative Verrucous Leukoplakia through Liquid Chromatography With Tandem Mass Spectrometry - Arroyo, Esteban [UNESP] (2023)
Proliferative verrucous leukoplakia (PVL) is an oral potentially malignant disorder associated with high risk of malignant transformation. Currently, there is no treatment available, and restrictive follow-up of patients is crucial for a better prognosis. Oral leukoplakia (OL) shares some clinical and microscopic features with PVL but exhibits different clinical manifestations and a lower rate of malignant transformation. This study aimed to investigate the proteomic profile of PVL in tissue and saliva samples to identify potential diagnostic biomarkers with therapeutic implications. Tissue and saliva samples obtained from patients with PVL were compared with those from patients with oral OL and controls. Label-free liquid chromatography with tandem mass spectrometry was employed, followed by qualitative and quantitative analyses, to identify differentially expressed proteins. Potential biomarkers were identified and further validated using immunohistochemistry. Staining intensity scan analyses were performed on tissue samples from patients with PVL, patients with OL, and controls from Brazil, Spain, and Finland. The study revealed differences in the immune system, cell cycle, DNA regulation, apoptosis pathways, and the whole proteome of PVL samples. In addition, liquid chromatography with tandem mass spectrometry analyses showed that calreticulin (CALR), receptor of activated protein C kinase 1 (RACK1), and 14-3-3 Tau-protein (YWHAQ) were highly expressed in PVL samples. Immunohistochemistry validation confirmed increased CARL expression in PVL compared with OL. Conversely, RACK1 and YWHA were highly expressed in oral potentially malignant disorder compared to the control group. Furthermore, significant differences in CALR and RACK1 expression were observed in the OL group when comparing samples with and without oral epithelial dysplasia, unlike the PVL. This research provides insights into the molecular mechanisms underlying these conditions and highlights potential targets for future diagnostic and therapeutic approaches.